Percutaneous cryoablation of kidney tumors after partial nephrectomy - Wojciech Krajewski; Maciej Guziński; Wojciech Tomczak; Łukasz Nowak; Jan Łaszkiewicz; Joanna Chorbińska; Adam Chełmoński; Katarzyna Grunwald; Bartosz Małkiewicz; Tomasz Szydełko (Videosurgery and Other Miniinvasive Techniques)
Introduction: The widespread use of ultrasound and cross-sectional imaging has led to a steady increase in the incidental discovery of renal masses. Most of them are treated with partial nephrectomy (PN), as recommended by the European Association of Urology guidelines. However, this approach carries a risk of local recurrence. In such a case, surgical reintervention can be more challenging and is often associated with worse prognosis. In this context, percutaneous ablative therapies are a promising alternative.